Partisipasi Petani Dalam Pengembangan Padi Varietas Hibrida Sterling di Subak Batuan Dangin Kecamatan Sukawati Kabupaten Gianyar - LESTARI, I DEWA AYU NYOMAN SRI JULIANA; DIARTA, I KETUT SURYA; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p13, 2023)
Farmer’s Participations in the Hybrid Rice Sterling Variety Development in Subak Batuan Dangin, Sukawati District, Gianyar Regency The increasing population will increase the amount of food consumption for rice needs. One of the innovations in agriculture is Sterling hybrid rice. The development of Sterling hybrid rice certainly cannot be separated from the participation of farmers. The objective of this study was to analyze farmer’s participations in the development of Sterling hybrid rice varieties and to figure out the factors that affects the participation. This research is a qualitative research. Data was collected using in-depth interviews, observation and documentation. The key informant in this study were 13 people. Data analysis in this study is descriptive qualitative. Based on the results of the research, at the decision-making stage farmers have been involved in all aspects of activities for decision-making, at the implementation stage farmers generally have followed the implementation activities in accordance with the agreement that was taken, at the stage of enjoying the results the farmers were satisfied with this development, and at the evaluation stage farmers provided input and suggestions. In terms of social factors are influenced by the age and education of farmers, economic factors are influenced by an increase in income and the amount of production, and technical factors are influenced by the way of maintenance.